Low Utilization of Insecticide-Treated Bed Net among Pregnant Women in the Middle Belt of Ghana. (30th July 2017) - Manu, Grace; Boamah-Kaali, Ellen Abrafi; Febir, Lawrence Gyabaa; Ayipah, Emmanuel; Owusu-Agyei, Seth; Asante, Kwaku Poku
Abstract : Background. Malaria in pregnancy leads to low birth weight, premature birth, anaemia, and maternal and neonatal mortality. Use of insecticide-treated nets (ITNs) during pregnancy is one of the proven interventions to reduce the malaria burden. However, Ghana has not achieved its target for ITN use among pregnant women. Methods. A qualitative study was conducted in seven communities purposively selected from the middle belt of Ghana. Participants who had delivered in the six months prior to this study were selected. In all, seven focus group discussions and twenty-four in-depth interviews were conducted between June and August 2010. Results. Respondents knew of the importance of ITNs and other malaria-preventive strategies. Factors such as financial access and missed opportunities of free distribution denied some pregnant women the opportunity to own or use an ITN. Reasons for not using ITNs during pregnancy included discomfort resulting from heat, smell of the net, and difficulty in hanging the net. Participants maintained their ITNs by preventing holes in the nets, retreatment, and infrequent washing. Conclusion. Pregnant women know about the causes and prevention of malaria. However, this knowledge is not transformed into practice due to lack of access to ITNs and sleeping discomforts among other logistical constraints.